Clinical characteristics of biopsy-proven renal sarcoidosis in Japan - Kamata, Yoshinori; Sato, Hiroshi; Joh, Kensuke; Tsuchiya, Yoshinori; Kunugi, Shinobu; Shimizu, Akira; Konta, Tsuneo; Baughman, Robert P; Azuma, Arata (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Background: Although some articles have described renal sarcoidosis, the incidence among biopsy cases remains unclear. Here, we defined the incidence of renal sarcoidosis among renal biopsy cases and analyzed the clinical course. Methods: We performed an epidemiological study examining renal biopsy cases treated at 5 centers between January 2000 and September 2015 and identified 16 cases (7 men, 9 women; mean (±SD) age, 59.4±18.6 years) out of a total of 14191 renal biopsy cases. Renal involvement of sarcoidosis was defined as granulomatous tubulointerstitial nephritis, tubulointerstitial nephritis without granulomatous lesions, and renal calcinosis. Fifteen of the cases were treated with steroid therapy. One case initially received steroid pulse therapy. The outcome was evaluated based on the estimated glomerular filtration rate (eGFR), CKD stage, and the change in eGFR (ΔeGFR) after treatment. A favorable response was defined as ΔeGFR ≥25%. Results: The incidence of renal sarcoidosis was 0.11%. The mean eGFR was 28.2±16.1 mL/min/1.73 m². At the last observation, the mean eGFR was 43.7±19.7 mL/min/1.73 m2. Although a favorable response to steroid therapy was found in the majority of cases (10/15, 67%), 12 of the 15 cases (80%) had residual renal dysfunction at the last observation and 8 cases (53%) had moderate to severe renal dysfunction. Conclusion: Renal sarcoidosis is extremely rare among renal biopsy cases. Among cases with an unfavorable response to steroid therapy, pathogenetic mechanisms other than sarcoidosis and severe nephron damage were observed.